PENDAMPINGAN DAN PEMBUATAN VIDEO PROFILE WISATA DESA CISAN-TANA SEBAGAI SALAH SATU PROMOSI WISATA DI KABUPATEN KUNINGAN - Sigit Setya Kusuma; Febby Fajar Nugraha (IKIP SILIWANGI, 2020)
Cisantana Village is located in Cigugur subdistrict, Kuningan Regency, West Java Province. Cisantana has abundant natural resources because of its geographical location on the slopes of Mount Ciremai. In addition to agricultural potential, Cisantana is also famous for cattle farming. Cisantana Village is a village that has very potential tourism potential. Village Cisantana is blessed with a lot of charm, a charm that must be explored and visualized through record media so that Cisantana Village has an audiovisual or can be called a video profile for tourism attraction to the community or tourists.